2011
DOI: 10.1149/1.3511787
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conductivity and Stability of Ba[sub 2]In[sub 2]O[sub 5] in Hydrogen Containing Atmospheres

Abstract: Ba 2 In 2 O 5 is one of the oxygen deficient ceramic materials widely investigated for both oxygen ion conduction and proton conduction in oxidizing atmospheres. However, its electrochemical properties have not been studied in hydrogen containing atmospheres. In this work, the electrical conductivity of Ba 2 In 2 O 5 in hydrogen containing atmospheres was investigated by ac impedance spectroscopy in the temperature range between 100 and 500°C and compared to its conductivity in air and nitrogen in order to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…Again, for the as-prepared BIO sample, an effect of water was noticed, in this case as a sharp increase in conductivity. When present, water in the structure is in interaction with the oxygen vacancies and oxygen ions [12,34]. When water is released, hydrogen incorporates directly and interacts with the free oxygen vacancies and ions, significantly improving conductivity.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, for the as-prepared BIO sample, an effect of water was noticed, in this case as a sharp increase in conductivity. When present, water in the structure is in interaction with the oxygen vacancies and oxygen ions [12,34]. When water is released, hydrogen incorporates directly and interacts with the free oxygen vacancies and ions, significantly improving conductivity.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
“…When water is released, hydrogen incorporates directly and interacts with the free oxygen vacancies and ions, significantly improving conductivity. The mechanisms are suggested in the literature [12][13][14]34]. The decomposition or reduction of the material were excluded as possible causes for increased conductivity, as no changes in composition or structure were observed by XRD after the test in hydrogen.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Undoped and Ce-doped Ba 2 In 2 O 5 are reported to show oxygen ion conductivity in oxygen and nitrogen atmospheres, as well as protonic conductivity in humid air and hydrogen-containing atmosphere, especially at temperatures below 500…”
mentioning
confidence: 99%
“…• C. 34 The hydrogen concentration cell condition in their study was as follows: In that study, emf was only observed under a humidified atmosphere. For this non-doped Ba 2 In 2 O 5 , the estimated t H + decreased with increasing temperature, and t H + = 0.74 at 350…”
Section: Improvement Of T H + By Doping With Pr In Bamentioning
confidence: 99%